Factores de las dificultades de financiación de las PyMES en Latinoamérica - Morini Marrero, Sandra (2015)
This article provides an analysis of the determinants of credit constraints in Latin American SMEs, for which each firm has been classified as NCC (Not Credit Constrained) if it has enough capital and FCC (Full Credit Constrained) if it has applied for bank credit but it was rejected or if it has not applied for external banking founds due to the terms and conditions.In this investigation the Enterprise Survey (ES) 2010 from the World Bank was used and Latin American SMEs were selected. In order to provide proofs about, which are the variables that influence in the probability of being NCC, a logistic regression analysis was made. This analysis was broken down in two levels: for each subsample country and in a general way. In this last case, firstly it was carried out a cluster analysis in order to group the countries and take into account their differences in terms of economic development and banking sector structure was carried out.In relation, to the logistic regression results, it can be highlighted that the variables “Quality-Certification”, “Sector” and “Sales Level” are significant (p <0,01, p <0,01 y p <0,05, respectively) and all of them have a positive relationship with the dependent variable (NCC).